Pengaruh Produktivitas Desa Wisata Dan Knowledge Management Terhadap Keberlanjutan Usaha (Studi Empiris Pada Balkondes Di Borobudur) - Septian Dwi Candra; Marisa Tri Hana; Nur Aisah Nugraheni; Dianah Shofiyani; Ilfi Nurfadhilah; Muhdiyanto (Universitas Muhammadiyah Metro, 2025)
Tourist villages are a tourism potential that can have a positive impact on economicdevelopment and environmental sustainability. This research aims to identify the influence oftourist village productivity on business sustainability and the influence of knowledgemanagement on business sustainability. The research method used is a quantitative method.The population in this study were Balcondes and BUMDES managers in 20 Balcondes inBorobudur. The sample of this research was 165 respondents using a purposive samplingmodel, namely distributing questionnaires. The analytical tool used in this research ismultiple linear analysis with the help of a data processing application, namely SPSS 23. Theresearch results show that the productivity of tourist villages has a positive effect on businesssustainability, apart from that, knowledge management also has a positive effect on businesssustainability